Implementation of Marketing Mix Strategy at Soelastri Dental and Oral Hospital - Sari, Retno; Theo, Deli; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Dental and oral health has an effect on improving the quality of life and productivity of human resources. RSGM Soelastri is one of the dental and oral health service facilities. The condition of visits of inpatients and new emergency room patients in 2024 has fluctuated and is below the target. This can result in a decrease in hospital revenue and can have an impact on the disruption of hospital operational activities, so that the services provided to patients are not optimal. Therefore, it is necessary to conduct a review of the marketing strategy of RSGM Soelastri. The purpose of this study is to analyze the implementation of marketing strategies at Soelastri Dental and Oral Hospital. This research uses a qualitative method, through in-depth interview techniques. Data sources are obtained from primary data and secondary data. There were 14 informants, divided into 8 main informants and 6 supporting informants. Data analysis by checking the results of the research with different data collection techniques, namely interviews, observations, and documentation. The results of the study are known that RSGM Soelastri has carried out segmentation, targeting and market positioning. RSGM Soelastri has carried out promotional activities such as counseling, but it has not been maximized. Promotion has not reached all levels of society. The types of services offered are complete. Service rates are able to compete with other hospitals. RSGM Soelastri includes staff in various types of training, but it is still limited. The tools used are modern, but there are some computer devices and radiology printers that are no longer efficient for service. There are limited human resources and financial constraints. The conclusion of this study is that the implementation of marketing strategies consisting of market segmentation, target market, positioning, and market surveys has been carried out, but not optimally. The implementation of the 7P Marketing Mix at RSGM Soelastri has been carried out, but it has not been maximized. The implementation of marketing strategies is constrained by budgets and human resources. It is suggested for other researchers, it is necessary to conduct research on marketing strategies in more depth by looking at the promotion mix of inpatient and emergency room services as one of the services that support the number of patient visits at RSGM Soelastri.